Ab Initio Study of Lithium-Boron and -Aluminum Hydrides Nanoparticles - Michos, Fotios; M. Sigalas, Michalis (Current Nanomaterials, 2016)
Background: Hydrogen is considered as the fuel of the future since it has about three times higher energy per mass relative to gasoline. However, it is difficult to be stored and there is intense effort to find materials that can store as much as possible hydrogen. Lithium-Aluminium and -Boron hydrides are some of the most important compounds used in hydrogen storage with promising hydrogen weight percentages and low desorption energies. Methods: The Density Functional Theory (DFT) have been used to calculate the desorption energies of Hydrogen in Lithium-Aluminium, and -Boron nanoparticles. Results: The type of nanoparticles studied were LinMnHxn with M = Al or B, n varying from 1 up to 20 and x between 0 and 4. Complex nanoparticles LinAln-yByH4n have been also examined. These type of nanoparticles try to combine the low weight of LinBnH4n with the low desorption energies of LinAlnH4n. Finally, NanAlnH4n nanoparticles have been studied. For all these cases, several different geometries were examined and the lowest energy geometry was chosen. Conclusion: For the fully hydrogenated NPs (x=4), the desorption energy reduces as n increases saturating to about 135 and 47 kJ/mol for Li20B20H80 and Li20Al20H80, respectively, in close agreement with measurements.
Keywords: density functional theory